2010
DOI: 10.1016/j.molcel.2010.05.014
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assembly of Plant RNA-Induced Silencing Complexes Facilitated by Molecular Chaperone HSP90

Abstract: RNA-induced silencing complexes (RISCs) play central roles in posttranscriptional gene silencing. In plants, the mechanism of RISC assembly has remained elusive due to the lack of cell-free systems that recapitulate the process. In this report, we demonstrate that plant AGO1 protein synthesized by in vitro translation using an extract of evacuolated tobacco protoplasts incorporates synthetic small interfering RNA (siRNA) and microRNA (miRNA) duplexes to form RISCs that sequester the single-stranded siRNA guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
302
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(319 citation statements)
references
References 50 publications
14
302
0
3
Order By: Relevance
“…Efficient RISC assembly requires the incorporation of small RNAs in both animal and plant cells (34)(35)(36). Thus, we selected mutations that are known to affect miRNA biogenesis and accumulation, including mutations in the doublestranded RNA-binding protein DRB1 (also known as HYL1) and Dicer homolog DCL1 mediating processing of most miRNA precursors (37,38), the RNA methyltransferase HEN1 (39) critical for miRNA stability and HASTY (HST), the Arabidopsis ortholog of Exp5 required for the nuclear export and/or stability of miRNAs (40).…”
Section: Resultsmentioning
confidence: 99%
“…Efficient RISC assembly requires the incorporation of small RNAs in both animal and plant cells (34)(35)(36). Thus, we selected mutations that are known to affect miRNA biogenesis and accumulation, including mutations in the doublestranded RNA-binding protein DRB1 (also known as HYL1) and Dicer homolog DCL1 mediating processing of most miRNA precursors (37,38), the RNA methyltransferase HEN1 (39) critical for miRNA stability and HASTY (HST), the Arabidopsis ortholog of Exp5 required for the nuclear export and/or stability of miRNAs (40).…”
Section: Resultsmentioning
confidence: 99%
“…HSP90 plays important roles in plant defense, especially in defense against microbial pathogens (Hubert et al, 2003;Takahashi et al, 2003;Sangster and Queitsch, 2005;Zhang et al, 2015). HSP90 also is implicated in chaperoning AGO1 (Iki et al, 2010). Our double mutant and expression analyses, however, suggest a synergistic, rather than a simple epistatic or additive, relationship.…”
Section: Discussionmentioning
confidence: 62%
“…It has been proposed that the chaperone machinery supports a loading-competent state of fly Ago2, allowing it to accept siRNA duplexes from Dcr-2-R2D2 (Miyoshi et al, 2010;Iwasaki et al, 2015). In plants, studies using tobacco BY-2 lysate demonstrated that HSP90 binds to Arabidopsis AGO1 and AGO4 and promotes the loading of sRNA duplexes (Iki et al, 2010;Ye et al, 2012). The cochaperones of HSP90 are capable of modulating the ATP-hydrolyzing rate of HSP90, recruiting client proteins, or playing chaperone roles on their own (Röhl et al, 2013).…”
Section: Loading Of Small Rnas Into Ago Family Proteinsmentioning
confidence: 99%